Glomerular Organization of the Antennal Lobes of the Diamondback Moth, Plutella xylostella L. - Yan, Xizhong; Wang, Zhiyu; Xie, Jiaoxin; Deng, Caiping; Sun, Xuejun; Hao, Chi (Frontiers in Neuroanatomy, 2019)
The antennal lobe of the moth brain is the primary olfactory centre processing information concerning pheromones and plant odours. Plutella xylostella is a major worldwide pest of cruciferous vegetables and its behaviour is highly dependent on their olfactory system. However, detailed knowledge of the anatomy and function of the P. xylostella olfactory system remains limited. In the present study, we present the 3-Dimentional (3-D) map of the antennal lobe of P. xylostella, based on confocal microscopic analysis of glomerular segmentation and Neurobiotin backfills of Olfactory Receptor Neurons (ORNs). We identified 74-76 ordinary glomeruli and a macroglomerular complex (MGC) situated at the entrance of the antennal nerve in males. The MGC contained three glomeruli. The volumes of glomeruli in males ranged from 305.83±129.53 to 25440.00±1377.67 μm3. In females, 74 -77 glomeruli were found, with the largest glomerulus ELG being situated at the entrance of the antennal nerve. The volumes of glomeruli in females ranged from 802.17±95.68 to 8142.17±509.46 μm3. Sexual dimorphism was observed in anomalous supernumerary, anomalous missing, shape, size, and array of several of the identified glomeruli in both sexes. All glomeruli, except one in the antennal lobe (AL), received projections of antennal ORNs. The glomeruli PV1 in both sexes received input from the labial palp nerve and was assumed as the labial pit organ glomerulus (LPOG). These results provide a foundation for better understanding of coding mechanisms of odours in this important pest insect.